Interkulturelle Theologie und Kulturwissenschaft Untersucht am Beispiel afrikanischer Theologie - Jahnel, Claudia (W. Kohlhammer GmbH, 2015)
Current global changes and a profound awareness of the problem regarding the thematic field of intercultural theology require new approaches. This book combines fundamental insights of the new research paradigm in the horizon of African Theology. In consequent cultural studies orientation of Intercultural Theology, central concepts of current cultural studies debates "time", "space", "body" and "agency" are taken up and their reflections in the discourse field of African theology are examined. African theology emerges as a product of relationship history with a persisting, varied dynamic and contested cultural power of interpretation. This book makes an important contribution to the current debate about the reorganization of theological discipline "intercultural theology". Aktuelle globale Veränderungen und ein fundiertes Problembewusstsein hinsichtlich des Themenfelds der Interkulturellen Theologie erfordern neue Zugangsweisen. Dieser Band verbindet grundlegende Einsichten des neuen Forschungsparadigmas im Horizont afrikanischer Theologie. In konsequent kulturwissenschaftlicher Orientierung Interkultureller Theologie werden zentrale Begriffe der gegenwärtigen kulturwissenschaftlichen Debatte "Zeit", "Raum", "Körper" und "agency", aufgegriffen und ihre Spiegelungen im Diskursfeld afrikanischer Theologie untersucht. Afrikanische Theologie tritt als Produkt einer Verflechtungs- und Beziehungsgeschichte mit anhaltender, wechselvoller Dynamik und umkämpfter kultureller Deutungsmacht hervor. Das Buch leistet einen wichtigen Beitrag zur aktuellen Diskussion um die Neugestaltung der theologischen Disziplin Interkulturelle Theologie